Пять забавных медвежат - Бондаренко Владимир Николаевич (Тридесятые сказки, 2006)
Экземпляры: Ф. 2 (20191126) / Инвентарный номер: 44116 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 81 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6